Neo-liberalism and Competitiveness: The Reflexive Principle of Contemporary Reason of Enterprise - Mas, Fernando Francisco (2022)
Nowadays, some of the social studies that approach neo-liberalism as a rationality tend to see competition as its central principle. This is particularly due to Michel Foucault’s study of the microeconomic school of German Ordoliberalism in the late 1970s. In this way, Foucault approached competitive action from an economistic - regulatory market logic and left aside theories on the formation of entrepreneurial behavior necessary to beat the rival. The latter refers to strategic management and its concept of competitiveness, which condenses the idea of permanently strengthening companies to win. The aim here is to develop a genealogical scheme of business strategy to ask whether “competitiveness” and not “competition” is the reflexive principle of contemporary neo-liberalism or “reason of enterprise”.